Abrupt policy reversal amid Black Lives Matter: Starbucks' grande employee dress code problem. Issue 5 (25th November 2021) - Douglas, Megan; Holtzen, Sarah; Ruane, Sinéad G.; Sherman, Kim; Williamson, Aimee
Abstract : Theoretical basis: Organizational Justice Theory serves as a useful frame for discussion of this case, focusing on perceptions of fairness in the workplace. Such perceptions are shaped by outcomes, procedures, information and interpersonal treatment. Perceptions of justice in these four dimensions are associated with job performance, citizenship behaviors and some mental health outcomes. The Exit, Voice, Loyalty, Neglect (EVLN) Model outlines four potential responses (exit, voice, loyalty and neglect) to perceived job dissatisfaction, serving as a useful framework for students to discuss potential employee reactions to Starbucks' decisions. Research methodology: This case was developed from secondary sources, including news reports, company annual reports and websites. The case has been classroom tested with undergraduate students in Principles of Management (online and face-to-face) Human Resource Management (online asynchronous) and Labor/Management Relations (online synchronous). Case overview/synopsis: In June 2020, Starbucks became immersed in controversy when its dress code policy conflicted with its public support for national protests over police brutality against Black Americans, including the death of George Floyd while in police custody. While publicly supporting the protests in a series of tweets, an internal memo forbidding employees from wearing Black Lives Matter attire was leaked to the press, generating national outcry, threats of a boycott and forcing Starbucks to reverse course immediately. This case examines the benefits and challenges of a corporate dress/uniform policy, and the implications of corporate involvement in social justice issues. Complexity academic level: This case can be used in a wide range of undergraduate and graduate courses, but particularly in Principles of Management and Human Resources courses.